ответ:1)3х+18-х-2х-18
3х-х-2х=18-18
0=0
2)6-3х-3-7+х
-3х+х=-6+3+7
-2х=4/*(-1)
2х=-4
х=-2
3)8х+3-10х+6-9
8х-10х=-3-6+9
-2х=0/*(-1)
2х=0
х=0
4)5-2х+2+4+х
х-2х=-5-2-4
-х=-11/*(-1)
х=11
5)7х+1-9х-3+5
7х-9х=-1+3-5
-2х=-3/*(-1)
2х=3
х=1 1/2
6)3,4+2у-7у+16,1
2у-7у=-3,4-16,1
-5у=-19,5/*(-1)
5у=19,5
у=3,9
7)20х+8-30х+30+15
20х-30х=-8-30-15
-10х=-53/*(-1)
10х=53
х=5,3
8)4х-4-4х+16+12
0=16-4-12
0=12-12
0=0
9)5,6-6+1,2х-1,6х+0,4
1,2х-1,6х=6-5,6-0,4
0,4х=0,4-0,4
0,4х=0
х=0
10)5х-60+6х-60-х+1
5х+6х-х=60+60-1
10х=119
х=11,9
Пошаговое объяснение:
/*(-1)-умножение на -1 знаки меняются на противоположные